Viability of seed balls for large-scale restoration of native plant communities in New Zealand - James W. Griffiths; Janice M. Lord; Jessica Paull; Aimee S. E. Pritchard; Andrew Butler; Jennifer Alderton-Moss; Karin van der Walt; Anja McDonald; Kirsty Moran (New Zealand Journal of Botany, 2025)

Physical properties of seed ball formulations - Janice M. Lord; Jessica Paull; Aimee S. E. Pritchard; Andrew Butler; James W. Griffiths (New Zealand Journal of Botany, 2025)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

To Measure is to Know: A Perspective on the Work of Dr. Margareta Hammarlund-Udenaes - Jessica I. Griffith; William F. Elmquist (Pharmaceutical Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Liposomal Irinotecan Accumulates in Metastatic Lesions, Crosses the Blood-Tumor Barrier (BTB), and Prolongs Survival in an Experimental Model of Brain Metastases of Triple Negative Breast Cancer - Afroz S. Mohammad; Jessica I. Griffith; Chris E. Adkins; Neal Shah; Emily Sechrest; Emma L. Dolan; Tori B. Terrell-Hall; Bart S. Hendriks; Helen Lee; Paul R. Lockman (Pharmaceutical Research, 2018)

Erratum to: Perseveration in a spatial-discrimination serial reversal learning task is differentially affected by MAO-A and MAO-B inhibition and associated with reduced anxiety and peripheral serotonin levels - Peter Zhukovsky; Johan Alsiö; Bianca Jupp; Jing Xia; Chiara Giuliano; Lucy Jenner; Jessica Griffiths; Errin Riley; Sajeed Ali; Angela C. Roberts; Trevor W. Robbins; Jeffrey W. Dalley (Psychopharmacology, 2017)

Perseveration in a spatial-discrimination serial reversal learning task is differentially affected by MAO-A and MAO-B inhibition and associated with reduced anxiety and peripheral serotonin levels - Peter Zhukovsky; Johan Alsiö; Bianca Jupp; Jing Xia; Chiara Guiliano; Lucy Jenner; Jessica Griffiths; Errin Riley; Sajeed Ali; Angela C. Roberts; Trevor W. Robbins; Jeffrey W. Dalley (Psychopharmacology, 2017)

Moss stable isotopes (carbon-13, oxygen-18) and testate amoebae reflect environmental inputs and microclimate along a latitudinal gradient on the Antarctic Peninsula - Jessica Royles; Matthew J. Amesbury; Thomas P. Roland; Glyn D. Jones; Peter Convey; Howard Griffiths; Dominic A. Hodgson; Dan J. Charman (Oecologia, 2016)

Planning adaptation to climate change in fast-warming marine regions with seafood-dependent coastal communities - Alistair J. Hobday; Kevern Cochrane; Nicola Downey-Breedt; James Howard; Shankar Aswani; Val Byfield; Greg Duggan; Elethu Duna; Leo X. C. Dutra; Stewart D. Frusher; Elizabeth A. Fulton; Louise Gammage; et al. (Reviews in Fish Biology and Fisheries, 2016)

Characterization of passive permeability at the blood–tumor barrier in five preclinical models of brain metastases of breast cancer - Chris E. Adkins; Afroz S. Mohammad; Tori B. Terrell-Hall; Emma L. Dolan; Neal Shah; Emily Sechrest; Jessica Griffith; Paul R. Lockman (Clinical & Experimental Metastasis, 2016)

Bottom‐up regulation of malaria population dynamics in mice co‐infected with lung‐migratory nematodes - Emily C. Griffiths; Karen Fairlie‐Clarke; Judith E. Allen; C. Jessica E. Metcalf; Andrea L. Graham (Ecology Letters, 2015)
When and how populations are regulated by bottom up vs. top down processes, and how those processes are affected by co‐occurring species, are poorly characterised across much of ecology. We are especially interested in the community ecology of parasites that must share a host. Here, we quantify how resources and immunity affect parasite propagation in experiments in near‐replicate ‘mesocosms’’ – i.e. mice infected with malaria ( Plasmodium chabaudi ) and nematodes ( Nippostrongylus brasiliensis ). Nematodes suppressed immune responses against malaria, and yet malaria populations were smaller in co‐infected hosts. Further analyses of within‐host epidemiology revealed that nematode co‐infection altered malaria propagation by suppressing target cell availability. This is the first demonstration that bottom‐up resource regulation may have earlier and stronger effects than top‐down immune mechanisms on within‐host community dynamics. Our findings demonstrate the potential power of experimental ecology to disentangle mechanisms of population regulation in complex communities.

Invited review: climate change impacts in polar regions: lessons from Antarctic moss bank archives - Jessica Royles; Howard Griffiths (Global Change Biology, 2015)
Mosses are the dominant plants in polar and boreal regions, areas which are experiencing rapid impacts of regional warming. Long‐term monitoring programmes provide some records of the rate of recent climate change, but moss peat banks contain an unrivalled temporal record of past climate change on terrestrial plant Antarctic systems. We summarise the current understanding of climatic proxies and determinants of moss growth for contrasting continental and maritime Antarctic regions, as informed by 13C and 18O signals in organic material. Rates of moss accumulation are more than three times higher in the maritime Antarctic than continental Antarctica with growing season length being a critical determinant of growth rate, and high carbon isotope discrimination values reflecting optimal hydration conditions. Correlation plots of 13C and 18O values show that species ( Chorisodontium aciphyllum / Polytrichum strictum ) and growth form (hummock / bank) are the major determinants of measured isotope ratios. The interplay between moss growth form, photosynthetic physiology, water status and isotope composition are compared with developments of secondary proxies, such as chlorophyll fluorescence. These approaches provide a framework to consider the potential impact of climate change on terrestrial Antarctic habitats as well as having implications for future studies of temperate, boreal and Arctic peatlands. There are many urgent ecological and environmental problems in the Arctic related to mosses in a changing climate, but the geographical ranges of species and life‐forms are difficult to track individually. Our goal was to translate what we have learned from the more simple systems in Antarctica, for application to Arctic habitats.

Reproductive biology of wahoo, Acanthocybium solandri, off eastern Australia - Mitchell T. Zischke; Jessica H. Farley; Shane P. Griffiths; Ian R. Tibbetts (Reviews in Fish Biology and Fisheries, 2013)

Carbon isotope evidence for recent climate‐related enhancement of CO 2 assimilation and peat accumulation rates in Antarctica - Jessica Royles; Jérôme Ogée; Lisa Wingate; Dominic A. Hodgson; Peter Convey; Howard Griffiths (Global Change Biology, 2012)
Signy Island, maritime Antarctic, lies within the region of the Southern Hemisphere that is currently experiencing the most rapid rates of environmental change. In this study, peat cores up to 2 m in depth from four moss banks on Signy Island were used to reconstruct changes in moss growth and climatic characteristics over the late Holocene. Measurements included radiocarbon dating (to determine peat accumulation rates) and stable carbon isotope composition of moss cellulose (to estimate photosynthetic limitation by CO 2 supply and model CO 2 assimilation rate). For at least one intensively 14 C‐dated Chorisodontium aciphyllum moss peat bank, the vertical accumulation rate of peat was 3.9 mm yr −1 over the last 30 years. Before the industrial revolution, rates of peat accumulation in all cores were much lower, at around 0.6–1 mm yr −1 . Carbon‐13 discrimination (Δ), corrected for background and anthropogenic source inputs, was used to develop a predictive model for CO 2 assimilation. Between 1680 and 1900, there had been a gradual increase in Δ, and hence assimilation rate. Since 1800, assimilation has also been stimulated by the changes in atmospheric CO 2 concentration, but a recent decline in Δ (over the past 50–100 years) can perhaps be attributed to documented changes in temperature and/or precipitation. The overall increase in CO 2 assimilation rate ( 13 C proxy) and enhanced C accumulation ( 14 C proxy) are consistent with warmer and wetter conditions currently generating higher growth rates than at any time in the past three millennia, with the decline in Δ perhaps compensated by a longer growing season.

Changes in the choice of colorectal cancer screening tests in primary care settings from 7,845 prospectively collected surveys - Martin C. S. Wong; George K. John; Hoyee W. Hirai; Thomas Y. T. Lam; Arthur K. C. Luk; Jessica Y. L. Ching; Simon S. M. Ng; Francis K. L. Chan; Sian M. Griffiths; Joseph J. Y. Sung (Cancer Causes & Control, 2012)

Effects of an increase in summer precipitation on leaf, soil, and ecosystem fluxes of CO2 and H2O in a sotol grassland in Big Bend National Park, Texas - Lisa Patrick; Jessica Cable; Daniel Potts; Danielle Ignace; Greg Barron-Gafford; Alden Griffith; Holly Alpert; Natasja Van Gestel; Traesha Robertson; Travis E. Huxman; John Zak; Michael E. Loik; et al. (Oecologia, 2007)